Internationalization and Corporate Social Responsibility in Developing Countries: A Developed Country Influence - Enoh, Peace (2015)
Abstract Previous literature have consistently focused on the internationalization of multinational corporations into developing countries. In the same vain, past literature has constantly discussed the CSR of developed country firms and MNCs. While there has been a rise in the reporting of EMNCs internationalization, the literature has failed to discuss the effects of this expansion on the business practices of these firms. This dissertation seeks to analyse how internationalization affects the CSR practices of firms from developing countries. To do this, past literature was analysed and focused on the views of CSR and Internationalization in developing countries as well as CSR in developed countries to get an understanding of the differing business systems. The theoretical framework used was the institutional theory which explains the pressures existing within business systems that cause businesses to modify their practices. This was based upon the assumption that institutions affect the business practices of firms operating within them, all other factors such as firm and industry specific factors being equal. The methodology used was content analysis of banks’ annual reports from which findings revealed that firms conform to principles laid out to their subsidiaries in the host market and that they tend to mimic the business practices of competing firms. This was clearly evident in the CSR practice as reported in their annual reports.